(untitled) (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to evaluate the feeding behavior of sheep fed sugarcane silage enriched with increasing levels of detoxified castor bean meal. Twenty-four non-castrated male Santa Inês sheep with an average body weight of 25.34 kg and four months of age, were distributed in four treatments - 0, 7, 14 and 21% of the natural matter of detoxified castor bean meal in sugarcane silage. There was a linear increase (p < 0.05) in time spent eating and feeding and rumination efficiency (g MS and NDF/h) with the inclusion of castor bean meal in silage. However, there was a linear decreasing response for time spent resting (p < 0.05). Time spent ruminating, number of boluses per day and numbers of chews per day per bolus were not affected (p > 0.05) by the inclusion of castor bean meal. The addition of detoxified castor bean meal to sugarcane silage reduces time spent eating and increases feed and rumination efficiency in sheep.